2019
DOI: 10.1029/2019jc015085
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Occurrence, and Fate of Biogenic Dimethylated Sulfur Compounds in the Yellow Sea and Bohai Sea During Spring

Abstract: The spatial distributions of biogenic dimethylated sulfur compounds (BDSCs), including dimethylsulfide (DMS), dimethylsulfoniopropionate (DMSP), and dimethylsulfoxide, were determined in the Yellow Sea and Bohai Sea during a survey in April–May 2014 and the occurrence and fate of BDSCs in the surface seawater were investigated. The concentrations of DMS and DMSP were significantly correlated with the stocks of chlorophyll a and a decreasing trend was observed from the inshore to the offshore areas. In situ inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 83 publications
3
5
0
Order By: Relevance
“…Specifically, the two highest fluxes both appeared in the North Pacific intermediate water (ST0701: 15.95 μ mol m −2 d −1 ; ST0703: 22.55 μ mol m −2 d −1 ) and were linked to high DMS levels (3.87 and 2.83 nmol L −1 ) and high wind speeds (8.6 and 12.1 m s −1 ). Our flux estimates were similar to previous investigations in the Pacific Ocean (e.g., Aranami and Tsunogai 2004), but lower than those of shelf seas (e.g., Xu et al 2019), which may be due to the relatively low primary productivity in open ocean. However, given the vast area of the Pacific Ocean, it still contributed a significant portion of global DMS emissions.…”
Section: Resultssupporting
confidence: 90%
“…Specifically, the two highest fluxes both appeared in the North Pacific intermediate water (ST0701: 15.95 μ mol m −2 d −1 ; ST0703: 22.55 μ mol m −2 d −1 ) and were linked to high DMS levels (3.87 and 2.83 nmol L −1 ) and high wind speeds (8.6 and 12.1 m s −1 ). Our flux estimates were similar to previous investigations in the Pacific Ocean (e.g., Aranami and Tsunogai 2004), but lower than those of shelf seas (e.g., Xu et al 2019), which may be due to the relatively low primary productivity in open ocean. However, given the vast area of the Pacific Ocean, it still contributed a significant portion of global DMS emissions.…”
Section: Resultssupporting
confidence: 90%
“…The high biological activity in the CEECS facilitated the consumption of DMSPd, which generally serves as an ideal carbon source for oceanic heterotrophic bacteria (Malmstrom et al., 2004). In the case of DMS, the biological turnover time was much slower than that of DMSPd and generally remained around 1–2 days in both seasons, which was comparable to the past results in the Yellow Sea and the Bohai Sea (Xu et al., 2019) and western Pacific (Xu et al., 2021). Although there were significant differences in the seawater parameters among different sea areas, high concentrations and production levels of DMS were usually accompanied by vigorous bacterial metabolism, resulting in relatively stable DMS biological turnover times.…”
Section: Resultssupporting
confidence: 87%
“…In summer, as temperatures were generally higher, the increase in temperature may inhibit phytoplankton growth and BDSCs production instead, leading to a negative correlation between BDSCs and temperature. Positive correlations between biogenic BDSCs and Chl‐ a have been observed in many shelf seas and oceans (Xu et al., 2019; G. P. Yang & Tsunogai, 2005). As for the CEECS, only moderate correlations between Chl‐ a and BDSCs were observed, and only in summer.…”
Section: Resultsmentioning
confidence: 99%
“…These correlations showed that the production by phytoplankton was an important source of sulfur compounds. This result agreed with previous studies (Riseman & DiTullio, 2004;Xu et al, 2019;Zhang et al, 2014) which also observed positive relationships between Chl-a, DMS, and DMSP. Furthermore, although DMSOd was weakly correlated with Chl-a (r = 0.328, p < 0.05), we know it is also affected by terrestrial input and photochemical oxidation.…”
Section: Correlations Among Sulfur Compounds and Their Relationships ...supporting
confidence: 94%